Nutrient limitation of woody debris decomposition in a tropical forest: contrasting effects of N and P addition. (24th June 2015) - Chen, Yao; Sayer, Emma J.; Li, Zhian; Mo, Qifeng; Li, Yingwen; Ding, Yongzhen; Wang, Jun; Lu, Xiankai; Tang, Jianwu; Wang, Faming
Summary: Tropical forests represent a major terrestrial store of carbon (C), a large proportion of which is contained in the soil and decaying organic matter. Woody debris plays a key role in forest C dynamics because it contains a sizeable proportion of total forest C. Understanding the factors controlling the decomposition of organic matter in general, and woody debris in particular, is hence critical to assessing changes in tropical C storage. We conducted a factorial fertilization experiment in a tropical forest in South China to investigate the influence of nitrogen (N) and phosphorus (P) availability on woody debris decomposition using branch segments (5 cm diameter) of four species ( Acacia auriculaeformis, Aphanamixis polystachya, Schefflera octophylla, and Carallia brachiata ) in plots fertilized with +N, +P, or +NP, and controls. Fertilization with +P and +NP increased decomposition rates by 5–53%, and the magnitude was species specific. Contrary to expectations, we observed no negative effect of +N addition on decay rates or mass loss of woody debris in any of the four study species. Decomposition rates of woody debris were higher in species with lower C : P ratios regardless of treatment. We observed significant accumulation of P in the woody debris of all species in plots fertilized with +P and +NP during the early stages of decomposition. N release from woody debris of Acacia (N‐fixing) was greater in the +P plots towards the end of the study, whereas fertilization with +N had no impact on the patterns of nutrient release during decomposition. Synthesis : Our results indicate that decomposition of woody debris is primarily constrained by P availability in this tropical forest. However, contrary to expectations, +N addition did not exacerbate P limitation. It is conceivable that decay rates of woody debris in tropical forests can be predicted by C : P or lignin : P ratios, but additional work with more tree species is needed to determine whether the patterns we observed are more generally applicable. Abstract : Lay Summary